2014
DOI: 10.2141/jpsa.0130077
|View full text |Cite
|
Sign up to set email alerts
|

Culture Conditions for Maintain Propagation, Long-term Survival and Germline Transmission of Chicken Primordial Germ Cell-Like Cells

Abstract: Transplantation of primordial germ cells (PGCs), which are the progenitor cells of gametes, is a powerful tool for generation of transgenic chickens. However, the frequencies of transgene integration into the genome of purified PGCs still remain low. An in vitro culture system enabling chicken PGCs to propagate efficiently would be useful for efficient transgenesis of PGCs. In the present study, we optimized the culture conditions for chicken PGCs to enhance the proliferation and evaluated the germline transmi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 33 publications
0
22
0
Order By: Relevance
“…Chicken PGCs isolated from embryonic blood can be expanded in a complex medium containing chicken serum, fetal bovine serum (FBS), fibroblast growth factor 2 (FGF2), and buffalo rat liver (BRL) cell-conditioned medium on a feeder of either BRL cells or Sandoz inbred mouse-derived thioguanine-resistant and ouabain-resistant (STO) fibroblasts [9]. Several research groups revealed that FGF signaling is required for chicken PGC proliferation in vitro [18, 48, 49]. A recent study has suggested that the membrane-bound form of chicken stem cell factor 2 (SCF2), but not the secreted form of chicken SCF1, enhanced the propagation of chicken PGCs in cooperation with FGF2 [50].…”
Section: Long-term Culture Of Pgcsmentioning
confidence: 99%
See 1 more Smart Citation
“…Chicken PGCs isolated from embryonic blood can be expanded in a complex medium containing chicken serum, fetal bovine serum (FBS), fibroblast growth factor 2 (FGF2), and buffalo rat liver (BRL) cell-conditioned medium on a feeder of either BRL cells or Sandoz inbred mouse-derived thioguanine-resistant and ouabain-resistant (STO) fibroblasts [9]. Several research groups revealed that FGF signaling is required for chicken PGC proliferation in vitro [18, 48, 49]. A recent study has suggested that the membrane-bound form of chicken stem cell factor 2 (SCF2), but not the secreted form of chicken SCF1, enhanced the propagation of chicken PGCs in cooperation with FGF2 [50].…”
Section: Long-term Culture Of Pgcsmentioning
confidence: 99%
“…3. Outline of a poultry PGC-bank program., the procedures of ex situ conservation of poultry genetic resources consist of five steps; 1) collection of embryonic tissues containing PGCs from target lines or breeds, 2) purification or culture of PGCs, 3) PGC storage in liquid nitrogen, 4) PGC transplantation to sterilized recipient embryos, and 5) recovery of populations by mating of male and female recipients. To date, successful long-term culture of PGCs from various chicken breeds including indigenous breeds has been reported [9, 18, 22, 49]. Therefore, at least in the chicken, the major advantage of PGCs for use as a source of gene banking is that PGCs obtained from a single donor embryo would be amplified significantly in vitro prior to cryopreservation.…”
Section: Conclusion and Perspectives On A Potential Poultry Pgc Bankmentioning
confidence: 99%
“…Poultry regeneration using embryonic and somatic stem cells (Usui et al 2009), poultry cloning and generation of transgenic poultry (Leighton et al 2008;van de Lavoir et al 2006;Zhu et al 2005) should be one of the most important subjects (Park et al 2014). Improvement of the cell culture should also be critical (Miyahara et al 2014). Scientific knowledge (Nakamura et al 2007) and technological refinement (Barrangou et al 2015;Yamamoto et al 2007a) should open up new frontiers for poultry breeding.…”
Section: Resultsmentioning
confidence: 99%
“…They cultured PGCs isolated from embryonic blood on feeder cells derived from Sandoz inbred mouse-derived thioguanine-resistant and ouabain-resistant (STO) cells or Buffalo Rat Liver (BRL) cells in a culture medium containing basic fibroblast growth factor (bFGF) and stem cell factor (SCF). The usefulness of this culture method was confirmed by Macdonald et al (2010) and Miyahara et al (2014). Choi et al (2010) devised a feeder-free culture method for PGCs and found that bFGF is one of the key factors for the maintenance and proliferation of PGCs.…”
Section: Pgc Culturementioning
confidence: 93%